STRATEGI PEMASARAN PRODUK TABUNGAN SABAR DALAM MENINGKATKAN JUMLAH DANA PIHAK KETIGA DI KSPPS BMT NU CABANG JAMBESARI DARUS SHOLAH - Ainur Rohmah; Ita Marianingsih (JOURNAL OF SHARIA ECONOMICS, 2025)
KSPPS BMT NU Jambesari Darus Sholah Branch is a business entity engaged in fundraising and fund distribution, has several products offered in the form of savings and financing. In this article, the researcher focuses on savings products at BMT NU Jambesari Darus Sholah Branch, one type of several savings products available, with the provision that this type of savings product has a fairly large profit share compared to other savings products, which is 55% and withdrawals can only be made during the month of Ramadan, with an initial deposit of IDR 10,000 and a minimum of IDR 5,000 for subsequent deposits without any element of coercion when saving. This savings is held to make it easier for people to meet their needs before Eid, this type of savings is known as Eid savings or SABAR, the purpose of this study is to find out what strategies are used in marketing SABAR savings products so that they become superior products and can increase the amount of third party funds at BMT, by using qualitative methods with a case study approach to find out more deeply about the marketing strategies used, thus it was obtained that BMT NU Jambesari Darus Sholah Branch uses the 4P strategy, namely product, price, place, and promotion. in marketing the products they offer while still adhering to the principles of Islamic teachings based on the Qur'an and the Sunnah.